Sleep Tight Farm : A Farm Prepares for Winter - Doyle, Eugenie 1952-; Stadtlander, Becca (San Francisco : Chronicle Books, 2016)
It is December, and there are many things for the family to do around the farm to get it ready for winter.
Keywords: Farm life -- Juvenile fiction; Rural families -- Juvenile fiction; Winter -- Juvenile fiction; Farm life -- Fiction; Family life -- Fiction; Winter -- Fiction